OP005 Higher anti-TNF serum levels are associated with perianal fistula closure in Crohn's disease patients. (16th January 2018) - Strik, A; Löwenberg, M; Ponsioen, C; Gecse, K; Buskens, C; Bemelman, W; D'Haens, G
Abstract: Background: Anti-tumour necrosis factor (anti-TNF) agents are effective agents to treat perianal Crohn's disease (CD). Recent evidence suggests that CD patients with perianal fistulas need higher serum concentrations of infliximab (IFX) compared with patients without perianal CD in order to achieve disease control. Methods: We performed a retrospective survey of all CD patients receiving active treatment with IFX or adalimumab (ADL) at our centre with available serum concentrations of IFX and ADL in CD patients with perianal fistulas. Fistula closure was defined as absence of drainage at physical examination and/or fistula healing on magnetic resonance imaging. Anti-TNF serum concentrations were compared among patients with active and closed perianal fistulas. Only patients with an interval between physical fistula examination/imaging and serum anti-TNF serum level measurement not exceeding 4 weeks were included in the analysis. Patients who underwent surgical interventions (i.e. ligation of intersphincteric fistula tract surgery or faecal diversion procedure) between physical examination/imaging and measurement of anti-TNF serum levels and patients with internal fistulas were excluded. Results: Of 352 CD patients receiving IFX or ADA, 67 had a history of perianal fistula. Forty-seven out of 67 were treated with IFX. Median IFX serum concentrations at trough ([interquartile range]) were significantly higher in patients with closed fistula ( n = 32) compared with patients with active fistula ( n = 15): 6.0 µg/ml [5.4–6.9] vs. 2.3 µg/ml [1.1–4.0], respectively ( p < 0.001)). A similar outcome was seen in 19 of 67 patients treated with ADL (13 with closed fistula and 6 with active fistula) with median serum concentrations of 7.4 µg/ml [6.5–10.8] vs. 4.8 µg/ml [1.7–6.2] respectively; p = 0.003. There were no differences seen in IFX and ADL dose and intervals between patients with active draining fistula and closed fistula. Conclusions: We report an association between anti-TNF serum concentrations and fistula closure in CD patients. Dose reduction of anti-TNF in CD patients with perianal disease is contraindicated, despite quiescent luminal disease.